Factors Associated With Elevated Inflammatory Markers Prior to Shoulder Arthroplasty. Issue 1 (February 2022) - Kopechek, Kyle J.; Cvetanovich, Gregory L.; Everhart, Joshua S.; Frantz, Travis L.; Samade, Richard; Bishop, Julie Y.; Neviaser, Andrew S.
Background : Preoperative erythrocyte sedimentation rate (ESR) and C-reactive protein (CRP) ranges for several shoulder arthroplasty indications are not well understood. Purpose : We sought to compare preoperative ESR and CRP values for a variety of shoulder arthroplasty indications and evaluate risk factors for elevated preoperative ESR and CRP values. Methods : We conducted a retrospective cohort study of shoulder arthroplasty cases performed at a single academic medical institution from 2013 to 2018. Preoperative ESR and CRP values for 235 shoulder arthroplasties with various indications were recorded. Independent risk factors for elevated values (CRP > 10.0 mg/L and ESR > 30.0 mm/h) were determined via multiple variable logistic regression. Results : Patients undergoing shoulder arthroplasty for osteoarthritis had an ESR (mean ± SD) of 22.6 ± 17.8, with 29.8% of patients elevated, and a CRP of 6.5 ± 6.4, with 25.5% of patients elevated. Arthroplasty for acute fracture and prosthetic joint infection (PJI) had higher preoperative ESR and CRP values. Multivariate analysis identified several predictors of elevated ESR, including infection, acute fracture, diabetes, and female sex. It also identified predictors of elevated CRP, including infection, acute fracture, and younger age. Conclusions : Preoperative ESR and CRP values may be elevated in 25% to 30% of patients undergoing primary shoulder arthroplasty. Arthroplasty for both acute fracture and PJI, along with several other patient factors, was associated with elevated preoperative ESR and CRP. Thus, routine collection of ESR and CRP preoperatively may not be of benefit, as elevated values are common. Further study is warranted.